Intersectional lives : Chinese Australian women in white Australia - Kamp, Alanna (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Intersectional Lives explores the varied experiences of Chinese Australian women across time and place during the White Australia Policy era (1901-1973). This book will appeal to social and cultural geographers with additional audiences of interest in history and historical geography, ethnic and racial studies, gender studies, diaspora studies, migration studies, and gender and feminist studies"--
Keywords: Chinese -- Australia -- Social conditions; Women -- Australia -- Social conditions; White Australia policy; Australia -- Ethnic relations; Australia -- History -- 20th century; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Human Geography